A case report of melanotic neuroectodermal tumor of infancy complicated with congenital heart disease and hypothyroidism - Zuo, Hua-Chu; Huang, Jin-Yue; Hu, Xiao-Li; Zhao, Lin-Sheng (Frontiers in Cardiovascular Medicine, 2022)
To the best of our knowledge, thus far there are no reported cases of melanotic neuroectodermal tumor of infancy (MNTI) with multiple complications. In this case report, we describe the clinical phenotype of MNTI in a 9-month-old female infant associated with tetralogy of Fallot (TOF), a congenital heart defect, and congenital hypothyroidism (CH). Our study showed that the growth of MNTI was delayed by a lower dosage of levothyroxine (L-T4) that was prescribed to treat CH because of the presence of TOF, a severe congenital heart disease. However, the standardized dosage of L-T4 improved thyroid function but stimulated the rapid growth of MNTI. Our report demonstrated that treatment with L-T4 affects the progression of MNTI. Our findings demonstrated the role of thyroid hormone in MNTI growth and progression. Furthermore, our study suggested that the treatment of co-morbidities in children with MNTI requires careful consideration of their effects on the growth and progression of MNTI.